A novel microfluidic device to model the human proximal tubule and glomerulus. Issue 8 (16th January 2017) - Sakolish, Courtney M.; Mahler, Gretchen J.
Abstract : A novel multi-channel microfluidic device to model human glomerular filtration and proximal tubular re-uptake. Abstract : We have developed a re-usable multi-layer microfluidic device to model the human kidney that incorporates a porous growth substrate, physiological fluid flow, and the passive filtration of the glomerulus. The target cell line in this project is HK-2, immortalized human kidney proximal tubule cells. Cells were exposed to a shear stress of 0.8 dyne cm −2 within the device and monitored for protein expression, cytoskeletal reorganization, and increased molecular transport. Additionally, an endothelial cell-seeded glomerular filter was added to allow for more realistic "primary urine" within these devices. The results of this research suggest that cells grown within this microfluidic device exhibit more in vivo -like behaviour than those grown using traditional culturing methods, and that the filtration of serum proteins by the glomerulus is necessary for healthy cell function. The addition of this glomerulus-mimic to the device provides the first in vitro model of passive glomerular filtration coupled with the proximal tubule.